A Watermark Approach for Image Transmission: Implementation of Channel Coding Technique with Security - et.al, G.Aparna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper an approach for secured digital image transmission with watermark is being proposed. The tremendous growth in technology for various applications demand secured communications across the wireless channels. Secured image transmission is the one of the prominent process in digital communication applications. A watermark is embedded in to the image data that is to be protected from unauthorized users. The cryptographic algorithms chosen for secured transmission led to the need for hardware implementation. In the process of secured image transmission turbo encoder is proposed for error correction. The proposed approach is realized in terms of hardware for the digital logic size, area and power consumption using Xilinx 14.2 software. Synthesizing and implementation of verilog code on the target device xc6slx150-2fgg484 for timing constraints, device utilization and performance details. © 2020 Elsevier Ltd. All rights reserved. Selection and/or Peer-review under responsibility of International Conference on Mechanical, Electronics and Computer Engineering